Aboriginal health: agreement between general practitioners and patients on their health risk status and screening history - Jessica M. Stewart; Rob Sanson‐Fisher; Sandra Eades; Catherine D'Este (Elsevier, 2014)
Abstract Objective: To examine agreement between patients' self‐report and general practitioners' perception of their patients' health risk status and screening history. Methods: Patients attending an Aboriginal Community Controlled Health Service self‐reported via survey their health risk status and screening history, while waiting to see their general practitioner (GP). Following the consultation the GP completed a corresponding survey. Prevalence rates and rates of agreement using the kappa statistic were calculated for both self‐reported and GP‐reported risk status for smoking, at‐risk alcohol consumption and physical inactivity; and screening history for blood pressure, cholesterol, diabetes and cervical cancer. Results: Prevalence rates of health risks were similar from self‐report versus GP‐reported, yet differed on screening history. Patients who identified themselves as being at risk were often not the same as those identified by GPs. Agreement between patient and doctor was substantial for smoking, yet poor for at‐risk alcohol consumption and physical inactivity. Agreement was fair for cholesterol and cervical cancer screening, and slight for blood pressure and diabetes screening. Conclusions and implications: This study suggests that for effective preventive care, using self‐report for some health risks may be reliable, but less so for screening history. Greater assistance is needed in primary health care settings to identify patients who are at risk.